Intestinal tuft cell subtypes represent successive stages of maturation driven by crypt-villus signaling gradients - Julian R. Buissant des Amorie; Max A. Betjes; Jochem H. Bernink; Joris H. Hageman; Veerle E. Geurts; Harry Begthel; Dimitrios Laskaris; Maria C. Heinz; Ingrid Jordens; Tiba Vinck; Ronja M. Houtekamer; Ingrid Verlaan-Klink; et al. (Nature Communications)
Abstract Intestinal tuft cells are epithelial sentinels that trigger host defense upon detection of parasite-derived compounds. While they represent potent targets for immunomodulatory therapies in inflammation-driven intestinal diseases, their functioning and differentiation are poorly understood. Here, we reveal common intermediary transcriptomes among the previously described tuft-1 and tuft-2 subtypes in mouse and human. Tuft cell subtype-specific reporter knock-ins in organoids show that the two subtypes reflect successive post-mitotic maturation stages within the tuft cell lineage. In vitro stimulation with interleukin-4 and 13 is sufficient to fuel the generation of new Nrep+ tuft-1 cells, arising from tuft precursors (tuft-p). Subsequently, changes in crypt-villus signaling gradients, such as BMP, and cholinergic signaling, are required to advance maturation towards Chat+ tuft-2 phenotypes. Functionally, we find chemosensory capacity to increase during maturation. Our tuft subtype-specific reporters and optimized differentiation strategy in organoids provide a platform to study immune-related tuft cell subtypes and their unique chemosensory properties.